Формування еколого-економічного механізму маркетингового управління в аграрному виробництві - Багорка, Марія Олександрівна; Bagorka, Mariya (Дніпровський державний аграрно-економічний університет, 2016)
Доведено, що сьогодні людство щодалі більше усвідомлює необхідність докорінної перебудови взаємовідносин суспільного виробництва з навколишнім природним середовищем. Адже складна екологічна ситуація в країні спонукає як виробників, так і споживачів до пошуку оптимального співвідношення між рівнем власного прибутку та рівнем витрат на природоохоронну діяльність. У зв’язку з цим формування та подальший розвиток екологічно орієнтованого аграрного сектору економіки в Україні робить питання екологічного маркетингу та посилення його ролі у процесі ведення сільськогосподарського виробництва украй необхідним та актуальним. Brought today humanity a little rather anymore realizes the necessity of native alteration of mutual relations of public production with a natural environment. In fact a difficult ecological situation in a country induces both producers and consumers to the search of optimal betweenness by the level of own profit and level of charges on nature protection activity. In this connection forming and further development ecologically oriented agrarian to the sector of economy in Ukraine does the question of the ecological marketing and strengthening of his role in the process of conduct of agricultural production very a necessity and actual. Agrarian politics inUkrainemust be built in accordance with new modern requirements, principles, standards of quality of leading ecology-economic and social world tendencies and requirements. An important step on this way is development of mechanism of ecology-economic management in an agrarian production. The ecological marketing that will provide adaptation of main processes of marketing management taking into account nature protection requirements must become the important constituent of such mechanism, and also will allow to take into account in the process of production the requirement of man in ecological safety.For effective introduction of ecology-economic mechanism of marketing management it is necessary to take into account the features of all his elements at effective cooperation of natural, productive, social factors and features of marketing management in an agrarian production.
Forming of ecology-economic mechanism of marketing management is in agrarian production
Keywords: екологічний маркетинг; ecological marketing; еколого-економічне управління; ecology-economic management; аграрне виробництво; agrarian production; екологічно безпечна продукція; ecologically safe products; соціальна відповідальність; social responsibility